Complete denture hygiene and nocturnal wearing habits among patients attending the Prosthodontic Department in a Dental University in Brazil - Takamiya, Aline Satie [UNESP]; Monteiro, Douglas Roberto [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Pero, Ana Carolina [UNESP] [UNESP]; Compagnoni, Marco Antonio [UNESP]; Barbosa, Débora de Barros [UNESP] (Wiley-Blackwell, 2011)
Complete denture hygiene and nocturnal wearing habits among patients attending the Prosthodontic Department in a Dental University in BrazilObjective:The aim of this study was to evaluate the overnight wearing and cleaning habits of complete denture wearers.Background:Successful complete denture treatment can be achieved when the patients are motivated and aware of appropriate denture wear and hygiene.Materials and methods:A sample of 224 complete denture wearers (162 women) aged 37-89 years was studied. Inclusion criteria comprised edentulous subjects who had received their new complete dentures between 2000 and 2005 in the Dental Clinic of the Aracatuba and Araraquara Dental School, São Paulo State University. Ethical approval was sought and granted. Subjects were interviewed using questions related to overnight denture wearing and denture cleaning habits. Possible statistical relationships among some of items were analysed by the chi-square test at 5% significance level.Results:Of the patients, 55.8% removed their dentures during the overnight period and 88% did this every day. Among them, 66.4% removed both dentures. Most of the patients used brushing with toothpaste (105 patients - 46.87%) as a cleaning method. More than a half of the subjects (63.4%) showed biofilm and calculus on their dentures.Conclusion:The patients need instructions and motivation concerning denture hygienic and denture removal overnight.
Keywords: complete denture; denture hygiene; denture cleanser; elderly